We Go on a Ferry - Mattern, Joanne, 1963- (Egremont, MA : Red Chair Press, 2020)
"What to expect from a trip on a ferry boat"--Provided by publisher.
Includes index
Keywords: Ferries -- Juvenile literature; Transportation -- Juvenile literature